Synthesis and catalytic applications of ruthenium(ii)–phosphino-oxime complexes. Issue 45 (19th April 2016) - Francos, Javier; Menéndez-Rodríguez, Lucía; Tomás-Mendivil, Eder; Crochet, Pascale; Cadierno, Victorio
Abstract : Ruthenium complexes containing a phosphino-oxime ligand have been synthesized, and their catalytic utility for the rearrangement of aldoximes, as well as for the α-alkylation/reduction of acetophenones with primary alcohols, demonstrated. Abstract : In this work, the preparation of the first ruthenium complexes containing a phosphino-oxime ligand is presented. Thus, the reaction of cis -[RuCl2 (DMSO)4 ] (3 ) with 2.4 equivalents of 2-Ph2 PC6 H4 CH{NOH (1 ) in refluxing THF led to the clean formation of the octahedral ruthenium(ii ) derivative cis, cis, trans -[RuCl2 κ 2 -( P, N )-2-Ph2 PC6 H4 CH{NOH2 ] (5 ), whose structure was unambiguously confirmed by means of a single-crystal X-ray diffraction study. Complex5 could also be synthesized from the reaction of the dimer [RuCl(μ-Cl)(η 6 -p-cymene)2 ] (4 ) with an excess of1 in refluxing toluene. Treatment of4 with 2 equivalents of1, in CH2 Cl2 at r.t., allowed also the preparation of the half-sandwich Ru(ii ) derivative [RuClκ 2 -( P, N )-2-Ph2 PC6 H4 CH{NOH(η 6 -p-cymene)][PF6 ] (6 ). In addition, complexes5 and6 proved to be active catalysts for the rearrangement of aldoximes to primary amides, as well as for the α-alkylation/reduction of acetophenones with primary alcohols, with the former showing the best performances in both processes.